Survei Sarana Dan Prasarana Pendidikan Jasmani Dan Tingkat Kesegaran Jasmani Siswa Kelas VIII SMP PGRI Barembeng Kabupaten Gowa - Saleh, M. Sahib; Ramdhani, Syahru (Journal Coaching Education Sports, 2020)
This study aims (1) to determine the state of the Facilities and Infrastructure of Physical Education at SMP PGRI Barembeng, Kab. Gowa, (2) to find out the Physical Fitness Level of Class VIII Students of SMP PGRI Barembeng, Kab. Gowa, (3) to determine the effect of facilities and infrastructure on the Physical Fitness Level of SMP PGRI Barembeng. This type of research is descriptive research. The population of this study were all SMP PGRI Barembeng Kab. Gowa The research sample consisted of 40 male students of class VIII SMP PGRI Barembeng. Data collection techniques using observation and tests. The data analysis technique used is descriptive statistics using computer facilities through the SPSS program. Based on data analysis, the results are obtained; (1) the condition of facilities and infrastructure that supports Physical Education learning at PGRI Barembeng Junior High School is categorized as ide, (2) the level of physical fitness of class VIII SMP PGRI Barembeng can be categorized as moderate, (3) there is an influence of facilities and infrastructure on the Physical Fitness Level of SMP PGRI Barembeng. Keywords: Facilities and Infrastructure, Physical Fitness Abstrak Penelitian ini bertujuan (1) Untuk mengetahui keadaan Sarana dan Prasarana Pendidikan Jasmani SMP PGRI Barembeng Kab. Gowa, (2) Untuk mengetahui Tingkat Kesegaran Jasmani Siswa Kelas VIII SMP PGRI Barembeng Kab. Gowa (3), Untuk mengetahui pengaruh sarana dan prasarana terhadap Tingkat Kesegaran Jasmani SMP PGRI Barembeng. Jenis penelitian ini adalah penelitian deskriptif. Populasi penelitian ini adalah semua SMP PGRI Barembeng Kab. Gowa. Sampel penelitian terdiri dari 40 orang siswa putra kelas VIII SMP PGRI Barembeng. Teknik pengumpulan data menggunakan observasi dan tes. Teknik analisis data yang digunakan adalah statistik deskriptif menggunakan fasilitas komputer melalui program SPSS. Berdasarkan analisis data diperoleh hasil: (1) Kondisi sarana dan prasarana yang mendukung pembelajaran penjas SMP PGRI Barembeng dikategorikan ideal, (2) Tingkat kesegaran jasmani kelas VIII SMP PGRI Barembeng dapat dikategorikan sedang, (3) Ada pengaruh sarana dan prasarana terhadap Tingkat Kesegaran Jasmani SMP PGRI Barembeng. Kata Kunci: Sarana dan Prasarana, Tingkat Kesegaran Jasmani